Molybdenum-based alloy with medium-high temperature oxidation resistance and preparation method thereof
A molybdenum-based alloy with Mo, Ti, Si, and C composition, optionally modified with Cr or Al, addresses the oxidation and toughness challenges by enhancing oxidation resistance and maintaining fracture toughness, effectively preventing catastrophic oxidation and reducing mass loss.
Patent Information
- Application Number
- CN202411322388.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
AI Technical Summary
Molybdenum-based alloys suffer from poor oxidation resistance and difficulty in balancing oxidation resistance with fracture toughness, particularly in the temperature range of 600-800°C, leading to catastrophic oxidation and reduced room temperature fracture toughness.
A molybdenum-based alloy composition comprising Mo, Ti, Si, and C, with Ti forming silicide for high-temperature strength and TiC for reduced density, and optionally modified with Cr or Al to enhance oxidation resistance, maintaining a ductile phase Mo ss volume fraction of at least 50% for toughness.
The alloy exhibits improved medium- and high-temperature oxidation resistance, preventing pest oxidation and reducing mass loss, with a dense oxide film, while maintaining good room temperature fracture toughness.
Smart Images

Figure CN119194194A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of alloys, and in particular to a molybdenum-based alloy with medium- and high-temperature oxidation resistance and a preparation method thereof. Background Art
[0002] Molybdenum (Mo)-based alloys are one of the important candidate materials for key hot-end components of aero-engines such as high-pressure turbine blades because of their high melting point, low thermal expansion coefficient, and excellent high-temperature mechanical properties. However, molybdenum-based alloys currently still have the problems of high density and poor oxidation resistance. In particular, the pest catastrophic oxidation phenomenon of molybdenum alloys in the temperature range of 600-800°C is one of the important problems that hinder their application. This is because the main oxidation products of molybdenum-based alloys are glassy silicon dioxide (SiO2) and molybdenum oxide (MoO3). Molybdenum oxide will volatilize rapidly when the temperature reaches 600°C and above, forming a large number of holes in the oxide layer of silicon dioxide, causing oxidation corrosion to continue to proceed to the interior of the alloy. The existing methods for improving the oxidation resistance of molybdenum-based alloys through alloy composition design are mainly to increase the silicon (Si) content in the alloy or add modifying elements such as chromium (Cr) and aluminum (Al). However, these methods will cause the ductile phase in the alloy - the molybdenum solid solution phase (MoO3). ss ) volume fraction is reduced, thus significantly reducing the room temperature fracture toughness of the material. Currently, there is no molybdenum-based alloy that takes into account both oxidation resistance and material toughness. Summary of the invention
[0003] In order to solve the above-mentioned problems in the prior art, the present invention provides a molybdenum-based alloy with medium- and high-temperature oxidation resistance and a preparation method thereof, so as to solve the problem that the existing molybdenum alloy has poor oxidation resistance and it is difficult to balance oxidation resistance and fracture toughness through alloy composition design. The composition design principle of the molybdenum-based alloy of the present invention is: the high-melting-point molybdenum element is the main body, the silicon element provides high-temperature oxidation resistance, and forms silicide with titanium element to provide high-temperature strength; the addition of a large amount of Ti element can significantly reduce the density of the alloy; the addition of a small amount of TiC ceramic phase can reduce the density while further supplementing the high-temperature strength of the alloy; the modifying elements chromium and aluminum further improve the medium- and high-temperature oxidation resistance of the alloy. This alloy consists of the ductile phase Mo ss , strengthening phase Ti5Si3 and TiC, the key point is the ductile phase Mo ss The volume fraction is not less than 50% to maintain good room temperature fracture toughness.
[0004] The complete technical solution of the present invention includes:
[0005] A molybdenum-based alloy with medium- and high-temperature oxidation resistance comprises four elements: Mo, Ti, Si and C. In terms of molar percentage, Ti is 35-45%, Si is 8-15%, C is 5-10%, and the balance is Mo.
[0006] Furthermore, when the alloy is oxidized at 800°C, its mass first decreases rapidly and then the mass decrease rate slows down; when oxidized at 1100°C, its mass first decreases rapidly and then increases slowly. After oxidation at 800°C and 1100°C for 24 hours, the thickness of the oxide film is 110 to 130 microns.
[0007] A molybdenum-based alloy with medium- and high-temperature oxidation resistance, comprising four elements of Mo, Ti, Si and C and a modifying element; the modifying element is any one or two of Cr and Al; in terms of molar percentage, Ti: 35-45%, Si: 8-15%, C: 5-10%, modifying element: 3-10%, and the balance is Mo.
[0008] Furthermore, the molybdenum-based alloy includes five elements: Mo, Ti, Si, C, and Cr; in terms of molar percentage, Ti: 35-45%, Si: 8-15%, C: 5-10%, Cr: 5-10%, and the balance is Mo.
[0009] Furthermore, after continuous oxidation at 800 °C for 24 h, the Cr-modified Mo-based alloy material did not undergo pest oxidation and the mass loss was no more than 2.0 mg / cm 2 After continuous oxidation at 1100℃ for 24h, the mass reduction is no more than 10.0mg / cm 2 In addition, the thickness of the oxide film after oxidation at 800°C for 24 hours is not higher than 10 microns; the thickness of the oxide film after oxidation at 1100°C for 24 hours is not higher than 80 microns.
[0010] Furthermore, the molybdenum-based alloy includes five elements: Mo, Ti, Si, C, and Al; in terms of molar percentage, Ti: 35-45%, Si: 8-15%, C: 5-10%, Al: 3-8%, and the balance is Mo.
[0011] Furthermore, the Al element modified molybdenum-based alloy material structure is Mo ss , Ti5Si3 and TiC three-phase composition, Al element modified molybdenum-based alloy material after continuous oxidation at 800℃ for 24h, no pest oxidation phenomenon occurs and the mass reduction is no more than 5.0mg / cm 2 After continuous oxidation at 1100℃ for 24h, the mass reduction is no more than 7.0mg / cm 2 In addition, the thickness of the oxide film after oxidation at 800°C for 24 hours is no more than 20 microns; and the thickness of the oxide film after oxidation at 1100°C for 24 hours is no more than 60 microns.
[0012] Furthermore, the molybdenum-based alloy includes six elements: Mo, Ti, Si, C, Cr, and Al; in terms of molar percentage, Ti: 35-45%, Si: 8-15%, C: 5-10%, Cr: 3-6%, Al: 0-4%, and the balance is Mo.
[0013] Furthermore, the molybdenum-based alloy structure is composed only of the ductile phase Mo ss , strengthening phase Ti5Si3 and TiC, ductile phase Mo ss The volume fraction is not less than 50%.
[0014] Furthermore, the molybdenum-based alloy structure is composed only of the ductile phase Mo ss , strengthening phase Ti5Si3 and TiC, ductile phase Mo ss The volume fraction of Cr is not less than 50%, and the Mo ss The metal / oxide interface of the phase forms a chromium and molybdenum rich transition zone.
[0015] Furthermore, the molybdenum-based alloy structure is composed only of the ductile phase Mo ss , strengthening phase Ti5Si3 and TiC, ductile phase Mo ss The volume fraction is not less than 50%, and the Al element forms a continuous TiO2-Al2O3 outermost layer on the surface of the oxide film.
[0016] Furthermore, the amount of the modifying element added does not exceed Mo ss The solid solubility limit in the ductile phase Mo ss , strengthening phases Ti5Si3 and TiC.
[0017] The method for preparing the molybdenum-based alloy with medium- and high-temperature oxidation resistance comprises the following steps:
[0018] (1) weighing raw materials according to the molar percentage of elements of the molybdenum-based alloy;
[0019] (2) placing the raw materials in a crucible and placing it in a vacuum arc melting furnace for melting, turning it over after the alloy cools down, repeating this operation 4 to 5 times to make the raw material composition uniform, and taking out the melted alloy in the crucible after cooling down to below 50° C. with the furnace;
[0020] (3) placing the alloy ingot into a heat treatment furnace and performing a homogenization treatment in an argon environment at 1600° C. for 10 to 100 hours to obtain a molybdenum-based alloy with good medium- and high-temperature oxidation resistance.
[0021] Preferably, the C in the alloy element in step (1) is weighed in the form of a TiC compound, and the Ti raw material in the alloy element needs to be weighed after deducting the Ti content in TiC;
[0022] Preferably, the vacuum arc melting furnace in step (2) is flushed with high-purity argon before use until there are no impurities in the furnace; after the vacuum arc melting furnace is flushed with no impurities, the vacuum in the furnace is made higher than 1.0E 4Pa.
[0023] Preferably, the raw materials in step (2) are placed in a crucible and put into a vacuum arc melting furnace for melting as follows: the pressure of the vacuum arc melting furnace is pumped to below 5×10E 4Pa, the vacuum arc melting furnace is turned on, and the vacuum arc melting furnace is slowly heated at a power of 25 to 30 kW; after 20 to 30 minutes, the power of the vacuum arc melting furnace is increased to 80 to 90 kW, the current is 450 to 550A, and the vacuum furnace is rapidly heated to 2000 to 2300°C for melting.
[0024] Preferably, argon gas is introduced during the smelting process in step (2), and the gas flow rate of argon gas is 0.1 Mpa.
[0025] Preferably, argon gas is introduced during the heat treatment in step (3), and the gas flow rate of argon gas is 0.3 Mpa.
[0026] Compared with the prior art, the present invention has the following advantages:
[0027] 1. The molybdenum-based alloy of the present invention has good room temperature fracture toughness, high temperature strength and oxidation resistance by rationally designing the alloy composition: the ductile phase Mo of not less than 50% volume fraction ss Good room temperature fracture toughness is ensured; the strengthening phases Ti5Si3 and TiC provide room temperature and high temperature mechanical properties and reduce density; Ti5Si3 also provides good high temperature oxidation resistance. In particular, the molybdenum-based alloy of the present invention overcomes the disadvantage of catastrophic oxidation "pest" of other molybdenum-based alloys in the 800°C medium temperature region, and also exhibits a lower oxidation rate in an air atmosphere of 1100°C.
[0028] 2. The molybdenum-based alloy of the present invention can further improve the medium and high temperature oxidation resistance of the alloy by adding the modifying elements chromium and aluminum. At a certain addition level, the Cr element will ss The metal / oxide interface of the phase forms a chromium and molybdenum enriched transition zone, and the addition of Al promotes the formation of a continuous TiO2-Al2O3 outermost layer on the surface of the oxide film. It should be noted that the amount of modified elements added should not exceed the Mo ss The solid solubility limit in the alloy is exceeded because the appearance of more intermetallic compound phases will impair the room temperature fracture toughness of the alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The microstructure of the molybdenum-based alloy prepared in Examples 1, 2 and 3 of the present invention.
[0030] Figure 2 The oxidation kinetics diagram of the molybdenum-based alloys prepared in Examples 1, 2, and 3 of the present invention.
[0031] Figure 3 The cross-sectional microstructure of the molybdenum-based alloys prepared in Examples 1, 2, and 3 of the present invention after being oxidized at 800° C. for 24 hours.
[0032] Figure 4 The cross-sectional microstructure of the molybdenum-based alloys prepared in Examples 1, 2, and 3 of the present invention after being oxidized at 1100° C. for 24 hours. DETAILED DESCRIPTION
[0033] The present invention is described in detail below in conjunction with the embodiments and drawings, but it should be understood that the embodiments and drawings are only used to exemplify the present invention and do not constitute any limitation on the protection scope of the present invention. All reasonable changes and combinations within the scope of the inventive concept of the present invention fall within the protection scope of the present invention.
[0034] Example 1
[0035] The molybdenum-based alloy with medium-to-high temperature oxidation resistance of this embodiment includes, by mole percentage, 40% Mo, 40% Ti, 15% Si, and 5% C.
[0036] A method for preparing a high entropy alloy with high temperature oxidation resistance comprises the following steps:
[0037] (1) preparing pure molybdenum (99.99%), pure titanium (99.995%), pure silicon (99.9999%), and TiC powder (99%, diameter 2-5 μm) as raw materials; weighing the raw materials according to the molar percentage ratio of 40% Mo, 35% Ti, 15% Si, and 5% TiC;
[0038] (2) The vacuum arc melting furnace is repeatedly flushed with high-purity argon gas twice to remove impurities in the furnace, thereby avoiding the introduction of impurity elements during the high-temperature process; before melting, the vacuum in the vacuum arc melting furnace is ensured to be higher than 1.0E-4Pa;
[0039] (3) Place the weighed raw materials in a crucible and then place it in a vacuum arc melting furnace. Then, pump the pressure in the vacuum arc melting furnace to below 5×10E-4Pa, turn on the power, and slowly heat the furnace at a power of 30KW. After heating for 20 minutes, slowly increase the power of the vacuum arc melting furnace to 85KW, and the current is 500-520A. During the melting process, argon gas is introduced, and the argon gas flow rate is 0.1MPa. After the melting is completed, the initial melted alloy ingot is cooled and turned over, and the melting is continued again. The melting process is repeated 5 times. After ensuring that the alloy composition is fully homogenized, turn off the power, and take out the alloy ingot when the furnace temperature drops below 50°C.
[0040] (4) The alloy ingot is placed in a heat treatment furnace and subjected to homogenization treatment in an argon environment at 1600° C. for 100 hours to obtain a molybdenum-based alloy with good medium- and high-temperature oxidation resistance.
[0041] The microstructure of the molybdenum-based alloy prepared in this example is as follows Figure 1 a, shown by Mo ss , Ti5Si3 and TiC three phases, among which Mo ss The volume fraction is greater than 50%.
[0042] The oxidation kinetics experiment is to conduct isothermal oxidation experiments on the molybdenum-based alloy samples prepared in this example, and continuously record the changes in sample mass. The phase composition of the oxide layer on the surface of the alloy is analyzed by an X-ray diffractometer, and the cross section of the oxide layer is observed using a scanning electron microscope with an energy spectrum. Figure 2 As shown in the figure, when the alloy is oxidized at 800℃, the mass decreases rapidly first, and then the decrease slows down and turns into a slow mass decrease. When oxidized at 1100℃, the mass decreases rapidly first, and then immediately turns into a slow mass increase, indicating that the oxide film begins to passivate. After oxidizing for 24 hours at both temperatures, the thickness of the oxide film reaches 110 to 130 microns, respectively. Figure 3 a. Figure 4 As shown in a.
[0043] It should be noted that the following embodiments all carried out this experiment and have similar rules, so the experimental process will not be repeated in the remaining embodiments. Some experimental results are selected here for illustration.
[0044] Example 2
[0045] The molybdenum-based alloy with medium-to-high temperature oxidation resistance of this embodiment includes, by mole percentage, 35% Mo, 40% Ti, 15% Si, 5% C and 5% Cr.
[0046] A method for preparing a high entropy alloy with high temperature oxidation resistance comprises the following steps:
[0047] (1) preparing pure molybdenum (99.99%), pure titanium (99.995%), pure silicon (99.9999%), TiC powder (99%, diameter 2-5 μm), and pure chromium (99.99%) as raw materials; weighing the raw materials according to the molar percentage of 35% Mo, 35% Ti, 15% Si, 5% TiC, and 5% Cr;
[0048] (2) The vacuum arc melting furnace is repeatedly flushed with high-purity argon gas twice to remove impurities in the furnace, thereby avoiding the introduction of impurity elements during the high-temperature process; before melting, the vacuum in the vacuum arc melting furnace is ensured to be higher than 1.0E-4Pa;
[0049] (3) Place the weighed raw materials in a crucible and then place it in a vacuum arc melting furnace. Then, pump the pressure in the vacuum arc melting furnace to below 5×10E-4Pa, turn on the power, and slowly heat the furnace at 30KW. After heating for 20 minutes, slowly increase the power of the vacuum arc melting furnace to 80KW, and the current is 450-500A. During the melting process, argon gas is introduced, and the argon gas flow rate is 0.1MPa. After the melting is completed, the initial melted alloy ingot is cooled and turned over, and the melting is continued again. The melting process is repeated 5 times. After ensuring that the alloy composition is fully homogenized, turn off the power, and take out the alloy ingot when the furnace temperature drops below 50°C.
[0050] (4) placing the alloy ingot into a heat treatment furnace and performing a homogenization treatment for 100 hours in an argon environment at 1600° C., thereby obtaining a Cr-modified molybdenum-based alloy with good medium- and high-temperature oxidation resistance.
[0051] The microstructure of the Cr element modified molybdenum-based alloy prepared in this example is as follows: Figure 1 b shown by Mo ss The alloy is composed of three phases: Ti5Si3 and TiC. The addition of Cr does not significantly change the alloy phase composition and the volume fraction of each phase. Figure 2 It can be seen that after continuous oxidation at 800℃ for 24h, the Cr-modified Mo-based alloy material prepared in this example did not undergo pest oxidation and the mass reduction was only 1.3mg / cm 2 After continuous oxidation at 1100℃ for 24h, the mass loss was only 3.9mg / cm 2 In addition, after oxidation at 800℃ for 24h, the thickness of the oxide film is less than 10 microns ( Figure 3 b); after oxidation at 1100℃ for 24h, the thickness of the oxide film is only about half of that of the unmodified alloy ( Figure 4 b). The above values are far lower than those of the unmodified molybdenum-based alloy, which proves that the Cr element modification also improves the medium and high temperature oxidation resistance of the molybdenum-based alloy.
[0052] Example 3
[0053] The molybdenum-based alloy with medium-to-high temperature oxidation resistance of this embodiment includes, by mole percentage, 35% Mo, 40% Ti, 15% Si, 5% C and 5% Al.
[0054] A method for preparing a high entropy alloy with high temperature oxidation resistance comprises the following steps:
[0055] (1) preparing pure molybdenum (99.99%), pure titanium (99.995%), pure silicon (99.9999%), TiC powder (99%, diameter 2-5 μm), and pure aluminum (99.999%) as raw materials; weighing the raw materials according to the molar percentage of 35% Mo, 35% Ti, 15% Si, 5% TiC, and 5% Al;
[0056] (2) The vacuum arc melting furnace is repeatedly flushed with high-purity argon gas twice to remove impurities in the furnace, thereby avoiding the introduction of impurity elements during the high-temperature process; before melting, the vacuum in the vacuum arc melting furnace is ensured to be higher than 1.0E-4Pa;
[0057] (3) Place the weighed raw materials in a crucible and then place it in a vacuum arc melting furnace. Then, pump the pressure in the vacuum arc melting furnace to below 5×10E-4Pa, turn on the power, and slowly heat the furnace at a power of 30KW. After heating for 20 minutes, slowly increase the power of the vacuum arc melting furnace to 80KW, and the current is 450-500A. During the melting process, argon gas is introduced, and the argon gas flow rate is 0.1MPa. After the melting is completed, the initially molten alloy ingot is cooled and turned over, and the melting is continued again. The melting process is repeated 5 times. After ensuring that the alloy composition is fully homogenized, turn off the power, and take out the alloy ingot when the furnace temperature drops below 50°C.
[0058] (4) placing the alloy ingot into a heat treatment furnace and performing a homogenization treatment for 100 hours in an argon environment at 1600° C., thereby obtaining an Al-modified molybdenum-based alloy with good medium- and high-temperature oxidation resistance.
[0059] The microstructure of the Al-modified molybdenum-based alloy material prepared in this example is as follows: Figure 1 As shown in c, represented by Mo ss The alloy is composed of three phases: Ti5Si3 and TiC. The addition of Al element does not significantly change the alloy phase composition and the volume fraction of each phase. Figure 2 It can be seen that after continuous oxidation at 800℃ for 24h, the Al-modified molybdenum-based alloy material prepared in this example did not undergo pest oxidation and the mass reduction was only 4.0mg / cm 2 After continuous oxidation at 1100℃ for 24h, the mass loss was only 0.9mg / cm 2 In addition, after oxidation at 800℃ for 24h, the thickness of the oxide film is about 20 microns ( Figure 3 c); and after oxidation at 1100℃ for 24h, the thickness of the oxide film was reduced by one third compared with the unmodified alloy ( Figure 4 c). The above values are far lower than those of unmodified molybdenum-based alloys, proving that the Al element modification also improves the high-temperature oxidation resistance of molybdenum-based alloys.
[0060] Example 4
[0061] The preparation method of this embodiment is the same as that of embodiment 2, but the alloy composition is different. The alloy composition, measured by mole percentage, includes Mo: 38%, Ti: 35%, Si: 12%, C: 5%, and Cr: 10%.
[0062] Example 5
[0063] The preparation method of this embodiment is the same as that of embodiment 2, but the alloy composition is different. The alloy composition, measured by mole percentage, includes Mo: 40%, Ti: 35%, Si: 12%, C: 5%, and Al: 8%.
[0064] Example 6
[0065] The alloy composition of this embodiment is the same as that of embodiment 2, but the preparation method is different, wherein the heat treatment temperature is 1500° C. and the time is 50 hours.
[0066] Example 7
[0067] The alloy composition of this embodiment is the same as that of embodiment 3, but the preparation method is different, wherein the heat treatment temperature is 1600° C. and the time is 10 hours.
[0068] In summary, the modified molybdenum-based alloy of the present invention has excellent medium- and high-temperature oxidation resistance. The molybdenum-based alloy before doping overcomes the medium-temperature pest oxidation problem of the molybdenum alloy while ensuring room-temperature fracture toughness through reasonable composition design, and improves the oxidation resistance of the alloy; at the same time, the modified elements chromium and aluminum further significantly improve the medium- and high-temperature oxidation resistance of the molybdenum-based alloy.
[0069] The above applications are only some implementation methods of the present application. For those skilled in the art, several modifications and improvements can be made without departing from the creative concept of the present application, and these all belong to the protection scope of the present application.
Claims
1. A molybdenum-based alloy with medium- and high-temperature oxidation resistance, characterized in that: The molybdenum-based alloy comprises four elements: Mo, Ti, Si and C. In terms of molar percentage, Ti is 35-45%, Si is 8-15%, C is 5-10%, and the balance is Mo.
2. A molybdenum-based alloy with medium- and high-temperature oxidation resistance, characterized in that: The molybdenum-based alloy comprises four elements, namely Mo, Ti, Si and C, and a modifying element; the modifying element is any one or two of Cr and Al; in terms of molar percentage, Ti: 35-45%, Si: 8-15%, C: 5-10%, modifying element: 3-10%, and the balance is Mo.
3. The molybdenum-based alloy with medium- and high-temperature oxidation resistance according to claim 2, characterized in that: The molybdenum-based alloy comprises five elements: Mo, Ti, Si, C and Cr. In terms of molar percentage, Ti is 35-45%, Si is 8-15%, C is 5-10%, Cr is 5-10%, and the balance is Mo.
4. The molybdenum-based alloy with medium- and high-temperature oxidation resistance according to claim 2, characterized in that: The molybdenum-based alloy comprises five elements: Mo, Ti, Si, C and Al; in terms of molar percentage, Ti: 35-45%, Si: 8-15%, C: 5-10%, Al: 3-8%, and the balance is Mo.
5. The molybdenum-based alloy with medium- and high-temperature oxidation resistance according to claim 2, characterized in that: The molybdenum-based alloy comprises six elements: Mo, Ti, Si, C, Cr and Al; in terms of molar percentage, Ti: 35-45%, Si: 8-15%, C: 5-10%, Cr: 3-6%, Al: 0-4%, and the balance is Mo.
6. A molybdenum-based alloy with medium- and high-temperature oxidation resistance according to any one of claims 1 to 6, characterized in that: The molybdenum-based alloy structure consists of a ductile phase Mo ss , strengthening phase Ti5Si3 and TiC, ductile phase Mo ss The volume fraction is not less than 50%.
7. A molybdenum-based alloy with medium- and high-temperature oxidation resistance according to any one of claims 2, 3 or 5, characterized in that: The molybdenum-based alloy structure consists of a ductile phase Mo ss , strengthening phase Ti5Si3 and TiC, ductile phase Mo ss The volume fraction of Cr is not less than 50%, and the Mo ss The metal / oxide interface of the phase forms a chromium and molybdenum rich transition zone.
8. A molybdenum-based alloy with medium- and high-temperature oxidation resistance according to any one of claims 2, 4 or 5, characterized in that: The molybdenum-based alloy structure consists of a ductile phase Mo ss , strengthening phase Ti5Si3 and TiC, ductile phase Mo ss The volume fraction is not less than 50%, and the Al element forms a continuous TiO2-Al2O3 outermost layer on the surface of the oxide film.
9. A molybdenum-based alloy with medium- and high-temperature oxidation resistance according to any one of claims 2 to 6, characterized in that: The amount of modified elements added should not exceed Mo ss The solid solubility limit of .
10. The method for preparing the molybdenum-based alloy with medium- and high-temperature oxidation resistance according to any one of claims 1 to 9, characterized in that: The steps include: (1) weighing raw materials according to the molar percentage of elements of the molybdenum-based alloy; (2) placing the raw materials in a crucible and placing it in a vacuum arc melting furnace for melting, turning it over after the alloy cools down, repeating this operation 4 to 5 times to make the raw material composition uniform, and taking out the melted alloy in the crucible after cooling down to below 50° C. with the furnace; (3) placing the alloy ingot into a heat treatment furnace and performing a homogenization treatment in an argon environment at 1600° C. for 10 to 100 hours to obtain a molybdenum-based alloy with good medium- and high-temperature oxidation resistance.
